2017
DOI: 10.1177/0018726716686819
|View full text |Cite
|
Sign up to set email alerts
|

Proactivity routines: The role of social processes in how employees self-initiate change

Abstract: Proactive work behaviors are self-initiated, future-focused actions aimed at bringing about changes to work processes in organizations. Such behaviors occur within the social context of work. The extant literature that has focused on the role of social context for proactivity has focused on social context as an overall input or output of proactivity. However, in this article we argue that the process of engaging in proactive work behavior (proactive goal-striving) may also be a function of the social context i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 78 publications
2
47
0
1
Order By: Relevance
“…Proactive workplace behavior can be defined as a “process whereby individuals recognize potential problems or opportunities in their work environment and self-initiate change to bring about a better future work situation” (Parker and Collins, 2010, p. 636). Employees’ proactive workplace behavior is getting increasingly important for organizations to adapt to a volatile business environment and obtain a competitive advantage (Vough et al, 2017). Drawing on self-determination theory (SDT) (Ryan and Deci, 2000a; Parker and Collins, 2010), our study uncovers the mediating mechanisms through which spiritual leadership influences proactive workplace behavior by suggesting organizational identification and psychological safety as two sequential mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Proactive workplace behavior can be defined as a “process whereby individuals recognize potential problems or opportunities in their work environment and self-initiate change to bring about a better future work situation” (Parker and Collins, 2010, p. 636). Employees’ proactive workplace behavior is getting increasingly important for organizations to adapt to a volatile business environment and obtain a competitive advantage (Vough et al, 2017). Drawing on self-determination theory (SDT) (Ryan and Deci, 2000a; Parker and Collins, 2010), our study uncovers the mediating mechanisms through which spiritual leadership influences proactive workplace behavior by suggesting organizational identification and psychological safety as two sequential mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our participants were obviously the initiators of their own power crafting processes. 'Taking control and aiming for change' (Vough et al, 2017: 1194) is a major underlying reason for individuals to show proactive behaviours, which also applies to the elements we have identified for the power crafting phenomenon. Finally, the power crafting phenomenon in our study also required individuals to get 'attuned to the broader social contexts' (Vough et al, 2017).…”
Section: Power Crafting As a Proactive Work Behaviourmentioning
confidence: 72%
“…From the perspective of human resources management, regular feedback from a superior, sharing objectives with workers, and an appreciation for initiative and leaders’ support [61] enables individuals to implement proactive conducts. Other research confirmed that organisational and social processes shape proactivity in terms of discussing ideas with managers, autonomy, and peer support, which enhance workers’ self-efficacy for proactivity and allows them to feel more confident about acting appropriately [62,63].…”
Section: Discussionmentioning
confidence: 98%